An omnichannel approach to retailing: demystifying and identifying the factors influencing an omnichannel experience. Issue 3 (26th May 2020) - Hickman, Ellie; Kharouf, Husni; Sekhon, Harjit
ABSTRACT: The purpose of this research is to identify the factors that influence an omnichannel experience. Omnichannel is an emerging approach to retailing that responds to the changing nature of how customers shop in alternation between online and offline shops, and the increasing use of digital devices (e.g. smartphones and tablets), as a consequence retailers are focusing and establishing a seamless integrated approach to their services. Omnichannel is now a hot topic in retailing but there is a lack of empirical studies into the factors that influence an omnichannel experience. Using a mixed methods approach, we propose and empirically test a conceptual model that identifies four factors influencing an omnichannel experience: brand familiarity; customisation; perceived value, and technology readiness. We conceptualise omnichannel to include three key channels; in-store, online and mobile. Two hundred and forty-six questionnaires were collected and analysed using PLS-SEM and 11 interviews were carried out with marketing/ omnichannel professionals. Our results indicate that brand familiarity has a strong influence on omnichannel (in-store, online and mobile) while perceived value has a negative impact on the mobile experience. Our results show that retailers need to consider multiple factors, such as brand familiarity, customisation, perceived value and technology readiness as influencing factors of an omnichannel experience, and plan the use of multiple touchpoints simultaneously to enhance their overall customer's experience. Although this study demonstrates the significant factors influencing an omnichannel experience, questions remain regarding the exact use of each touchpoint by customers and the extent of overlap between the touchpoints. which .